Влияние формы лопаток радиальных направляющих аппаратов на эффективность турбинных ступеней - Русанов, Роман Андреевич; Русанов, Андрей Викторович; Лампарт, Петр; Чугай, Марина Александровна; Курская, Наталия Марсовна (НТУ "ХПИ", 2016)
Рассмотрено влияние формы профиля лопаток радиальных направляющих аппаратов на эффективность высоконагруженной ступени турбины ORC со степенью понижения полного давления выше семидесяти. Показано, что наибольшую эффективность обеспечивает направляющий аппарат, построенный с использованием нового аналитического метода профилирования радиальных лопаток турбинных ступеней. Согласно с этим методом профиль задается в криволинейной системе координат, состоит из входной и выходной кромок, а также спинки и корытца, описанных кривыми 5-го и 4-го порядков соответственно.

It was carried out a study of radial stator blades profile shape influence on the efficiency of high-loaded ORC turbine stage with the degree of reduction of the total pressure above 70. Three variants of turbines with different types of stator blade profiles are considered: the profile developed using a standard method for axial blades; the "half-drop" profile and the profile developed using the proposed method. It is shown that stator developed with the use of new method of analytical profiling of radial stator blades provides highest efficiency. The profile of radial blades is determined in a curvilinear coordinate system and consists of the trailing and leading edges, and also of suction and pressure sides described by polynomial curves of the 5th and 4th order, respectively. The special form of blade-to-blade channels allows us to obtain a low level of profile and trailing edge losses, as well as wave losses of kinetic energy. In the stage with proposed in paper stator blade shape, the kinetic energy losses related to the enthalpy drop in the stage were decreased by 2,2 % compared to the profile of a classic shape, and by 1,1 % compared to the "half-drop" profile. Using of the high-loaded stage with a new type of stator blade profile allowed us to significantly improve the aerodynamic characteristics of the flow part in the whole stage.
Influence of radial stator blades form on efficiency of turbine stages
Keywords: радиально-осевая турбина; высоконагруженная ступень; проточная часть; аналитический метод профилирования; пространственное течение; численное моделирование; radial-axial turbine; high-loaded stage; flow part; spatial flow; numerical modeling